RANCANG BANGUN SISTEM VALIDASI IJAZAH BERBASIS QR-CODE - Ichsan; Ramadhani; Ahd Muhajir (J-Innovation, 2019)
A certificate of diploma is a student's graduation letter obtained after completing a diploma education. The certificate of diploma is used for various needs such as file completeness to applying for a job, the requirement for continuing to higher level education. In fact, there are many problems that occur on falsification the certificate. To solve these problems, a system for printing and validating diplomas is needed, where it is run with an android based QR-Code scanning system. This system is a very appropriate solution for the process of making a certificate of diploma and the validation process is done quickly and accurately